Protease-Activated Receptor 2 in inflammatory skin disease: current evidence and future perspectives - Fan, Mengjie; Fan, Xiaoyao; Lai, Yangfan; Chen, Jin; Peng, Yifan; Peng, Yao; Xiang, Leihong; Ma, Ying (Frontiers in Immunology, 2024)
Protease-activated receptor-2 (PAR2) is a class-A G protein-coupled receptor (GPCR) activated by serine proteases and is expressed by multiple tissues, including the skin. PAR2 is involved in the skin inflammatory response, promoting Th2 inflammation, delaying skin barrier repair, and affecting the differentiation of keratinocytes. It also participates in the transmission of itch and pain sensations in the skin. Increasing evidence indicates that PAR2 plays an important role in the pathogenesis of inflammatory skin diseases such as acne vulgaris, rosacea, psoriasis, and atopic dermatitis. Additional focus will be placed on potential targeted therapies based on PAR2. The Goal of this review is to outline the emerging effects of PAR2 activation in inflammatory skin disease and highlight the promise of PAR2 modulators.